Senior secondary school students' engagement within a blended learning course : an exploratory case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in e-learning at Massey University, Palmerston North, New Zealand - Bloomfield, Gaye (Massey University, 2016)
This research presents an exploration of student engagement within a blended learning course at a New Zealand secondary school. Growing numbers of secondary school students are participating in blended learning courses with both face-to-face and online teaching and learning experiences. However, the uptake and use of blended learning is not matched by an understanding of the nature of senior secondary students’ behavioural, emotional and cognitive engagement. There are also gaps in understanding about approaches to learning that aid student engagement in a blended learning context. To address this gap in the research, case study methodology was used over four weeks with seven Year 12 students and the teacher of their blended learning course. A qualitative analysis of observations, online usage, document analysis and interviews was undertaken to determine the nature of engagement within the blended learning activities available in one unit of learning. The findings suggest that engaging senior secondary students in a blended learning environment involves a carefully considered and complex mix of cognitively and emotionally engaging activities. Three mechanisms that aided engagement with learning in this blended learning context were the fostering of a learning purpose, the use of scaffolds and providing the opportunity for the learner to personalise their activities. This study contributes to the field of secondary school blended learning by supporting and deepening the literature base about how senior secondary students engage with blended learning activities.
Keywords: Blended learning; High school students; Secondary school students